2017
DOI: 10.17159/2413-3051/2017/v28i2a1740
|View full text |Cite
|
Sign up to set email alerts
|

The impact of residential rooftop solar PV on municipal finances: An analysis of Stellenbosch

Abstract: Electricity utilities throughout the world are responding to the increased uptake of rooftop solar photovoltaic (PV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The lack of support could be attributed to the fact that both municipalities and Eskom generate their revenue through selling conventional grid energy, hence, a transition to solar PV could compromise their income. For example, a study on the impact of grid connected solar PV on municipal revenue in Stellenbosch, found that municipality would lose about 0.6–2.4 % in revenue, if households transitioned to solar PV [ 83 ]. Municipalities in South Africa are responsible for selling about 40 % of energy and as part of diversifying the energy mix, efforts have been made to purchase energy from rooftop house-owners [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lack of support could be attributed to the fact that both municipalities and Eskom generate their revenue through selling conventional grid energy, hence, a transition to solar PV could compromise their income. For example, a study on the impact of grid connected solar PV on municipal revenue in Stellenbosch, found that municipality would lose about 0.6–2.4 % in revenue, if households transitioned to solar PV [ 83 ]. Municipalities in South Africa are responsible for selling about 40 % of energy and as part of diversifying the energy mix, efforts have been made to purchase energy from rooftop house-owners [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, technological developments, and the falling cost of technologies such as rooftop PV systems, batteries, solar roof tiles, etc., imply that electricity demand is becoming more elastic and households are becoming less reliant on utilities. This trend towards decentralized energy production will bring about significant structural changes to the electricity sector (Korsten et al 2017), globally and in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…A similar case study was done for the Stellenbosch municipality in South Africa. Korsten et al (2017) found that the municipality could have lost 2.4 per cent of its total municipal electricity revenue in the 2013-14 financial year if all households that were able to do so, from a technical perspective, had invested in rooftop solar PV. Unlike the current research, these studies focus on a particular area and technology.…”
Section: Literature Reviewmentioning
confidence: 99%